Malaysian accounting standards overload? / Mohd Azhar Osman - Osman, Mohd Azhar (Universiti Teknologi MARA Kedah, Sungai Petani, 2002)
Accounting standards dominate the accountant's woric. These standards are being constantly changed, deleted, and/or added to, both in Malaysia and abroad. Due to the nature of accounting standards, this paper will assess whether there is an issue of accounting standards overload in Malaysia. If any, this paper will determine the effect of standards overload on, both practitioners and users of financial information. The paper then attempts to suggest solutions to cope with financial reporting overload.